First report of Stemphylium lycopersici keratitis, a complex corneal infection case - Zixiang Zhao; Siyu Leng; Yuhao Zou; Lijuan Xiang; Yunke Li; Yi Liu; Chongyang Wang; Man Yu (Journal of Ophthalmic Inflammation and Infection)
Abstract Filamentous fungi are among the emerging causes of infections, although corneal infections caused by these fungi are rare, they can lead to severe clinical outcomes. In this report, we present the first documented case of keratitis caused by Stemphylium lycopersici, a filamentous hemipteran fungus of the Pleosporaceae family. A 66-year-old man presented conjunctival redness, irritation, and visual deterioration in his left eye, following a stone chip injury that occurred five months earlier. Despite multiple treatments, the causative pathogen remained unidentified, leading to worsening symptoms and significant vision loss. This deterioration led the patient to seek care at our hospital. An in vivo confocal microscopy (IVCM) examination suggested a fungal infection. Consequently, antifungal medications were administered, but the condition did not improve. Metagenomic next-generation sequencing (mNGS) examination of corneal scrapings revealed a mixed infection with S. lycopersici and human alphaherpesvirus 1. This definitive diagnosis facilitated the implementation of targeted therapy, leading to progressive symptomatic improvement. Early and rapid pathogen identification using mNGS analysis of corneal scrapings enables accurate management of infectious keratitis, contributing to visual recovery and reducing the risk of resistance to corneal pathogenic microbes.